Central bank communication that works: Lessons from lab experiments - Oleksiy Kryvtsov; Luba Petersen (Bank of Canada, 2019)
We use controlled laboratory experiments to test the causal effects of central bank communication on economic expectations and to distinguish the underlying mechanisms of those effects. In an experiment where subjects learn to forecast economic variables, we find that central bank communication has a stabilizing effect on individual and aggregate outcomes and that the size of the effect varies with the type of communication. Announcing past interest rate changes has the largest effect, reducing individual price and expenditure forecast volatility by one- and two-thirds, respectively; cutting half of inflation volatility; and improving price-level stability. Forward-looking announcements in the form of projections and forward guidance of upcoming rate decisions have less effect on individual forecasts, especially if they do not clarify the timing of future policy changes. Our evidence does not link the effects of communication to forecasters' ability to predict future nominal interest rates. Rather, communication is effective via simple and relatable backward-looking announcements that exert strong influence on less-accurate forecasters. We conclude that increasing the accessibility of central bank information to the general public is a promising direction for improving central bank communication.
Keywords: C9; D84; E3; E52; 330; Monetary policy implementation; Transmission of monetary policy